A comparative study of two polymorphs of bis(1‐hydroxy‐2‐methylpropan‐2‐aminium) carbonate. Issue 3 (25th February 2016) - Ben Nasr, Mahjouba; Aubert, Emmanuel; Espinosa, Enrique
Abstract : A new polymorph of bis(1‐hydroxy‐2‐methylpropan‐2‐aminium) carbonate has been formed by the capture of CO2 from the atmosphere and is compared with a previously reported polymorph. The two polymorphs exhibit similar layers of an alternating cation–anion–cation neutral structure in their molecular arrangements. Periodic theoretical density functional theory (DFT) calculations indicate that both polymorphs present very similar stabilities. Abstract : Alkanolamines have been known for their high CO2 absorption for over 60 years and are used widely in the natural gas industry for reversible CO2 capture. In an attempt to crystallize a salt of ( RS )‐2‐(3‐benzoylphenyl)propionic acid with 2‐amino‐2‐methylpropan‐1‐ol, we obtained instead a polymorph (denoted polymorph II) of bis(1‐hydroxy‐2‐methylpropan‐2‐aminium) carbonate, 2C4 H12 NO + ·CO3 2−, (I), suggesting that the amine group of the former compound captured CO2 from the atmosphere forming the aminium carbonate salt. This new polymorph was characterized by single‐crystal X‐ray diffraction analysis at low temperature (100 K). The salt crystallizes in the monoclinic system (space group C 2/ c, Z = 4), while a previously reported form of the same salt (denoted polymorph I) crystallizes in the triclinic system (space group P, Z = 2) [Barzagli et al. (2012). ChemSusChem, 5, 1724–1731]. The asymmetric unit of polymorph II contains one 1‐hydroxy‐2‐methylpropan‐2‐aminium cation and half a carbonate anion, located on a twofold axis, while the asymmetric unit of polymorph I contains two cations and one anion. These polymorphs exhibit similar structural features in their three‐dimensional packing. Indeed, similar layers of an alternating cation–anion–cation neutral structure are observed in their molecular arrangements. Within each layer, carbonate anions and 1‐hydroxy‐2‐methylpropan‐2‐aminium cations form planes bound to each other through N—H…O and O—H…O hydrogen bonds. In both polymorphs, the layers are linked to each other via van der Waals interactions and C—H…O contacts. In polymorph II, a highly directional C—H…O contact (C—H…O = 156°) shows as a hydrogen‐bonding interaction. Periodic theoretical density functional theory (DFT) calculations indicate that both polymorphs present very similar stabilities.